Testosterone therapy improves well being and psychological health. Issue 6 (November 2017) - Akerman, Jason; Kovac, Jason R.; Lipshultz, Larry I.
Abstract : Purpose of review: To ascertain whether testosterone therapy (TTh) improves psychological health and a sense of overall well being in a number of clinical domains. Recent findings: Recent work suggests small but durable and replicable improvements in the components of male health and well being. Summary: Symptomatic hypogonadism is frequently associated with decreased libido and fatigue that contributes to lowered overall quality-of-life and worsening psychological health. This manuscript will review the evidence behind the generalized benefits of TTh on overall male health as well as on depression and cognitive function in particular. Influence of TTh on body composition and its relationship to cardiovascular disease are also discussed in this overall context.